ROCK MUSIC AND NATIONAL IDENTITY IN HUNGARY - Milun, Kathryn (Surfaces, 1991)
Marxism and nationalism. The political form and meaning of the discourse of national identity in Hungary as it appears in popular culture. Hungarian rock and shamanpunk. The debate over the national flag.